Memory of Vladimir Longinovich Kazenas - Izbasar I. Temreshev (Acta Biologica Sibirica, 2024)
The article is dedicated to the memory of  Vladimir Longinovich Kazenas (1941–2024), Doctor of Biological Sciences, entomologist, researcher of fauna, biology and systematics of insects of Central Asia, participant of many expeditions, major specialist in digger wasps, hymenopterologist, who discovered and described tens of insect species new to science, the author of about 200 scientific works, including 30 popular science and scientific books.